Unraveling the Effect of Intrinsic Carbon Defects on Potassium Storage Performance. (28th September 2022) - Yuan, Fei; Shi, Conghao; Li, Qiaoli; Wang, Jian; Zhang, Di; Wang, Qiujun; Wang, Huan; Li, Zhaojin; Wang, Wei; Wang, Bo
Abstract: Defects engineering is an attractive strategy to improve the potassium storage performance of carbon anodes. The current studies mainly focus on the introduction of external defects via heteroatom doping, however, the exploration on the effect of intrinsic defects caused by the loss of atoms or distortion in the crystal lattice on potassium storage is still lacking to date. Hence, a series of carbon materials with different intrinsic defect levels are developed via a soft‐template assisted method. It is found that intrinsic defects content in carbon is synergistically determined by the application of template and pyrolysis temperature, and a higher defects content is more likely to expose enormous edge active sites. This greatly promotes K‐adsorption storage during surface‐induced capacitive process, and therefore a strong positive correlation between capacity/capacity retention and intrinsic defects content is confirmed. As a result, the electrode with maximum defects content realizes a good capacity and a rate capability with long cycle lifespan (225.9 mAh g −1 at 2 A g −1 over 2000 cycles). This study offers an insight into the role of intrinsic defects of carbon materials in potassium storage performance. Abstract : A series of carbons with different intrinsic defects level are synthesized. It is demonstrated that a higher defects content is more beneficial to increase capacitive contribution by offering enough edge sites and pores or voids, so a positive correlation between defects content and capacity/capacity retention is revealed. The resulting products with the highest defects concentration achieve an excellent cycling stability.